TABOO WORDS IN THE WOLF OF WALL STREET MOVIE DIRECTED BY MARTIN SCORSESE - Maulani Pangestu; Hanhan Rahmawatie; Arif Hidayat; Baiatun Nisa (Ennichi, 2020)
The purpose of this study is to analyze word usage i.e. taboo words in the movie The Wolf of Wall Street and this study uses the approach through Sociolinguistics. The film is 3 hours long and has found 34 words containing taboos. This research was conducted to identify the taboo words and its types. This study applies qualitative methods to describe the conditions in a film. Data in form speech is spoken, while the data context is from the video of the movie of The Wolf of Wall Street . The data are collected by selecting a dialog that contains taboo words after watching and using the transcript of the film as additional reference. The writers focus on the dialogue spoken by all characters in the film which contain taboo words. The results of this study are as follows. First, the found taboo words can be divided into three, namely (1) banned behavior, (2) banned topics and (3) banned terms. Second, the type of the taboo words can be divided into four types: (1) epithets are found seven times, (2) profanity are found six times, (3) vulgar are found ten times, and the last (4) obscenity are found eleven times.